PENINGKATAN KUALITAS LAYANAN ADMINISTRASI BAGI PENGUSAHA HOMESTAY LOKAL DI DESA WISATA TEMAJUK SAMBAS - Oktavianda, Melti; Larasati, Anistya Fitri; Fahrizal, Meizi; Herdiansyah, Dedi; Diah, Januardi M; Purba, Charlyna S; Muhani, Urai (LP2M STP Mataram, 2024)
Temajok Tourism Village in Sambas Regency has great potential as a tourist destination, but local homestay entrepreneurs face challenges in administrative services. Limitations in guest recording, financial management, and English proficiency hinder them from providing optimal services to tourists, especially international tourists. This Community Service Program aims to improve the quality of homestay administrative services in Temajok Tourism Village. The partners are local homestay entrepreneurs who are generally new to the business and have limitations in administrative practices. Through training and counseling, this Community Service will improve partners' abilities in guest recording, financial management, and the use of business English for administrative needs, reservations, and correspondence. It is expected to have a positive impact on improving the quality of homestay services and tourist satisfaction. By improving the quality of administrative services, it is hoped that homestays in Temajok Tourism Village can compete and make a significant contribution to the development of local tourism